2021
DOI: 10.1111/sms.13919
|View full text |Cite
|
Sign up to set email alerts
|

Aortic dilatation: Value of echocardiography in the systematic assessment of elite rugby players in the French National Rugby League (LNR)

Abstract: The value of echocardiography in the screening of athletes in addition to the electrocardiogram is debated and still unclear. 336 rugby players in French professional divisions (Top 14, Pro D2) were prospectively assessed with electrocardiogram and echocardiography. 75% were Caucasian, 16.4% Pacific Islanders, and 8.6% Afro‐Caribbean. Six (1.8%) players had electrocardiogram abnormalities, exclusively negative T waves. Twenty‐one (6.25%) of them had abnormal echocardiography findings: one possible early hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(105 reference statements)
0
1
0
Order By: Relevance
“…Rowing is characterized by a combination of dynamic and static exercise, with repetitive surges in arterial blood pressure that can explain the higher prevalence of aortic dilatation in this subset of master-level athletes. Rugby players have been recently identified as another group at risk of aortopathy [ 134 ]. Kay et al found an unexpectedly high prevalence (41%) of aortic root dilatation (>40 mm) in middle-aged (45 ± 13 years) former elite rugby players.…”
Section: Chronic Effectsmentioning
confidence: 99%
“…Rowing is characterized by a combination of dynamic and static exercise, with repetitive surges in arterial blood pressure that can explain the higher prevalence of aortic dilatation in this subset of master-level athletes. Rugby players have been recently identified as another group at risk of aortopathy [ 134 ]. Kay et al found an unexpectedly high prevalence (41%) of aortic root dilatation (>40 mm) in middle-aged (45 ± 13 years) former elite rugby players.…”
Section: Chronic Effectsmentioning
confidence: 99%